Inverse identification of heat source model parameters for laser-powder directed energy deposition of AISI H13 deposit on AISI H11 substrate - Bertrand, Johanna; Abbès, Fazilay; Bonnefoy, Hervé; Flan, Bruno; Abbes, Boussad (Material Forming – ESAFORM 2024, 2024)
Numerical modeling and simulation are very useful tools for assessing the impact of process parameters and predicting optimized conditions in Laser Directed Energy Deposition (LDED) processes. Heat source parameters have a great influence on the accuracy of numerical modeling for predicting temperature fields and residual stresses. This paper presents a coupled experimental-numerical procedure to determine the Goldak’s heat source model parameters. Graded single-clad tracks were printed with the laser beam power increased continuously at a constant powder feeding rate and scanning speed. Bead widths, heights, and penetration depths were measured at different locations along the deposited track and then used as experimental data for an inverse identification process using the FEA code ABAQUS and the optimizer iSIGHT. The obtained results show that the accuracy of the numerical model is increased with optimized parameters.